2008
DOI: 10.1007/s00702-008-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased phospholipase A2 activity in cerebrospinal fluid of patients with dementia

Abstract: Phospholipase A2 (PLA2) is involved in important aspects of dementia, for example neurotransmission and memory processing, membrane function, choline availability, and antioxidative defense. Reduced PLA2-activity has been reported so far in blood samples and postmortem neuronal tissue in Alzheimer disease. For the first time, we studied PLA2 in cerebrospinal fluid (CSF) in Alzheimer disease (AD), vascular (VD), and mixed Alzheimer/vascular dementia (MD). Intracellular PLA2 was assessed in CSF of 16 AD, 12 VD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…Intracellular acting (cytosolic) PLA 2 enzymes occur ubiquitary, are activated on demand, and are (as other serine esterases) able to pass the blood-brain barrier (Reiber, 2005). Once being activated, increased enzyme activity can be measured in blood serum and cerebrospinal fluid, and we have previously shown a close correlation of PLA 2 activity in serum and CSF (as obtained from lumbar puncture samples) in other patient cohorts (Smesny et al, 2008). The activity of PLA 2 measured in this study comprises cytosolic isoenzymes of groups (2) and (3).…”
Section: Introductionmentioning
confidence: 92%
“…Intracellular acting (cytosolic) PLA 2 enzymes occur ubiquitary, are activated on demand, and are (as other serine esterases) able to pass the blood-brain barrier (Reiber, 2005). Once being activated, increased enzyme activity can be measured in blood serum and cerebrospinal fluid, and we have previously shown a close correlation of PLA 2 activity in serum and CSF (as obtained from lumbar puncture samples) in other patient cohorts (Smesny et al, 2008). The activity of PLA 2 measured in this study comprises cytosolic isoenzymes of groups (2) and (3).…”
Section: Introductionmentioning
confidence: 92%
“…Ca ++ -dependent PLA2 is increased in AD CSF [36], decreased in AD cortex [31], and unaffected in AD cerebellum [31]. Ca ++ -independent PLA2 is decreased in both AD CSF [37] and AD cortex [31], and unaffected in AD cerebellum [31]. Clearly, further characterization of changes in the multiple isoforms of PLA2 in AD is required.…”
Section: Glycerophospholipidsmentioning
confidence: 99%
“…selective antibodies for in PLA 2 proteins in serum and in cerebrospinal fl uid (as obtained from lumbar puncture samples), and showed that the enzyme composition was identical ( Smesny et al 2008). Based on this result, we can assume that the fi ndings of this study relate closely to membrane lipid biochemistry within the CNS.…”
Section: Discussionmentioning
confidence: 68%